Ecological correlates of sedentary behavior in young children with Autism Spectrum Disorder. (October 2020) - Thomas, S.; May, T.; Barnett, L.M.; Papadopoulos, N.; McGillivray, J.; Rinehart, N.
Highlights: Sedentary behavior rates in Autism similar to typical children. Improving parent mental health may improve sedentary behavior in Autism. Higher levels of attention deficit-hyperactivity disorder associated with higher levels of sedentary behaviour. Abstract: Background: School age children with Autism Spectrum Disorder (ASD) are typically more sedentary than typically developing (TD) children. It is unknown whether such differences occur in the first years of school, and what mechanisms drive this difference. Method: Sedentary Behavior (SB) in four-to-seven-year-old children with and without ASD was examined using accelerometry to 1) determine if SB is higher in children with ASD compared to TD children 2) identify correlates that may inform interventions to improve health outcomes for children with ASD. Results: Children with ASD (n = 31) engaged in similar levels of SB as TD children (n = 23). Age (older), higher levels of Attention-Deficit/Hyperactivity Disorder (ADHD) symptomology, imaginary play (less), and quiet play (less) were all associated with higher levels of SB in children with ASD only. Conclusions: Understanding what correlates impact SB in the early years may help prevent the increase in SB that occurs in children with ASD as they age.